Clinical Evaluation of Gingivo-Periodontal Symptoms in Epstein-Barr Viral Infection - Simona Ionela Grigoras; Ioana Rudnic; Catalina Danila; Sorina Solomon; Silvia Martu (Romanian Society of Oral Rehabilitation, 2012)
Introduction Mononucleosis is an infectious disease caused by Epstein-Barr virus (EBV) and characterized clinically by fever, angina, adenosplenomegalie, haematological by leucocytosis with atypical mononucleosis and immunologic by appearance of specific and nonspecific antibody. The purpose of the study This clinical and statistical evaluation study aimed total gingivo-periodontal manifestations due to infectious mononucleosis generally correlated with clinical, laboratory examination results and general demographic characteristics. Material and methods We took a group study consisting of 95 people hospitalized with the diagnosis of infectious mononucleosis in which we evaluated the clinical aspects of muco-gingival lesions in correlation with oral lesions and the emergence stage of the infectious mononucleosis. Results Most cases 20.6% of the total study group showed at intraoral clinical examination haemorrhagic pickets, diffuse gingival erythema and a smaller percentage had gingivo-necrotic acute ulcerative stomatitis. Conclusions Acute human infection, transmission, usually benign, occurring more frequently in younger age (children and adolescents), infectious mononucleosis is characterized by clinical polymorphism, diagnostic difficulties, possible complications as well as the existence of possible relationships with other oral pathological entities (aggressive periodontitis) or systemic (Hodgkin disease), characters emphasizes the need for numerous clinical biological research on this disease.